Identification of Nutrient Deficiencies at Calcareous Soils for Maize - Nursyamsi, Dedi (JOURNAL OF TROPICAL SOILS, 2010)
Identification of nutrient deficiencies at calcareous soils for maize (D Nursyamsi): A pot experiment was conducted to identify nutrient deficiencies at calcareous soils for maize (Zea mays, L.) in green house of Indonesian Soil Research Institute using top soil (0-20 cm) samples taken from Bogor (Typic Hapludalfs) and Blora (Typic Haplustalfs). The experiment used Randomized Completely Block Design, minus one test with 12 treatments and three replications, as well as maize of P21 variety as plant indicator. The results showed that use of N, P, K, Zn, Cu, Fe, and Mn fertilizers increased soil macro nutrients, i.e.: soil total-N, Olsen-P, HCl-P, and HCl-K, as well as soil micro nutrients, i.e.: soil DTPA-Zn, Cu, Fe, and Mn at both tested soils. Use of maize straw compost increased soil organic-C, total-N, HCl-K, and exchangeable Ca at Typic Hapludalfs and increased only soil organic-C and total-N at Typic Haplustalfs. Use of animal manure compost increased soil organic-C, exchangeable Ca and Mg, and CEC. Use of N, P, K, S, Zn, Cu, Fe, and Mn fertilizers increased each plant nutrients uptake at the soils. Use of both organic matters increased plant N, P, K, and Fe uptake at Typic Hapludalfs as well as increased only plant N, P, and K uptake at Typic Haplustalfs. Identification result showed that maize growth suffered from N, P, and K deficiencies at Typic Hapludalfs as well as N and P deficiencies at Typic Haplustalfs. Beside the nutrients, soil organic matter was also found out as limiting factor for maize growth in the soils.